2005
DOI: 10.1177/107327480501200205
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies in the Treatment of Colorectal Cancers

Abstract: These dramatic successes have led to further clinical studies of targeted therapy in colorectal cancer, making it one of the most promising areas of cancer research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
(20 reference statements)
1
15
0
4
Order By: Relevance
“…Both bind to the extracellular domain of EGFR, thereby acting as competitive antagonists of the natural ligands, EGF and transforming growth factor ␣ [45,46]. As a result, these mAbs block EGFR-mediated signaling, leading to G 1 cell cycle arrest as a result of hypophosphorylation of the retinoblastoma protein [47]. In addition, these mAbs induce downregulation of EGFR expression on the cell surface [45].…”
Section: Epidermal Growth Factor Receptor-targeted Antibodies: Cetuximentioning
confidence: 99%
“…Both bind to the extracellular domain of EGFR, thereby acting as competitive antagonists of the natural ligands, EGF and transforming growth factor ␣ [45,46]. As a result, these mAbs block EGFR-mediated signaling, leading to G 1 cell cycle arrest as a result of hypophosphorylation of the retinoblastoma protein [47]. In addition, these mAbs induce downregulation of EGFR expression on the cell surface [45].…”
Section: Epidermal Growth Factor Receptor-targeted Antibodies: Cetuximentioning
confidence: 99%
“…2 Kaplan-Meier survival curves of (a) time to progression (TTP) and of (b) overall survival (OS) zumab has a lower affinity for EGFR. The binding affinity constant (Km) has been reported to be 10 −8 M for nimotuzumab, 10 −10 M for cetuximab and 10 −11 M for panitumumab [5,21,22]. A recent study suggested nimotuzumab could bind to EGFR with transient monovalent binding on cells with low levels of EGFR [23].…”
Section: Discussionmentioning
confidence: 99%
“…Severe anaphylaxis occurred in 2% of patients and acneiform rash in 80% [45]. Although the mechanism of the improved response in the combination arm is unclear, it may have been related to reduced irinotecan effux from malignant cells, induction of apoptosis or effects on DNA repair [46]. An interesting observation from the BOND-1 study was the observed association between high-grade skin reactions, response rate and TTP.…”
Section: Cetuximabmentioning
confidence: 94%